Challenges of Public Administration Accreditation in a Fragmented Institutional Setting: The Case of Europe - Christoph Reichard (Central European Public Administration Review)
The paper is dealing with accreditation in higher education in Europe, based on observations in the European public administration accreditation field. Considering the existing evidence, there are positive consequences of accreditation, such as improvement of programs and teaching quality. There are also problems and weaknesses, moreover some doubts about the accreditation results. The author also predicts that in the future there may be a trend towards more homogeneity of public administration programs in Europe.